When and Why Usury Should be Prohibited - Mayer, Robert (2013)
Usury ceilings seem indefensible. Their opponents insist these caps harm the consumers they are intended to help. Low ceilings are said to prevent the least advantaged agents from accessing legal credit and drive them into the black market, where prices are higher and collection methods are harsher. But in this paper, I challenge these arguments and show that the benefits of interest-rate limitations in the most expensive credit markets clearly outweigh the costs. The test case is payday lending. Deregulated pricing in this market produces negative externalities that justify usury restrictions. Unless prices are capped, the more solvent majority of borrowers is compelled to cross-subsidize the least solvent debtors, who have a high rate of default. Rationing the riskiest debtors out of this market by means of a moderate usury cap puts an end to this unfairness and produces fewer bad consequences than the advocates of deregulated pricing recognize. I argue that only an extreme principle like maximizing the minimum could justify a free market in payday credit.
Keywords: Usury; payday lending; Loan shark; Just price; Interest Rate; Credit